PAX9 mutation of non-syndromic hypodontia in a Malaysian family - Mohamed Idrus, Nur Farahiyah; Rosley, Nur Syahira; Irfanita, Nining; Ardini, Yunita Dewi; Ichwan, Solachuddin J. A.; Lestari, Widya (UI Proceedings Series, 2016)
Objective: Hypodontia is portrayed by the missing of one to six numbers of teeth. PAX9 is one of the genes that caused non-syndromic hypodontia. We aimed to investigate the PAX9 mutation of non-syndromic hypodontia with clinical variability in a Malaysian hypodontia family. Methods: Clinical examinations for all participants whilst orthophantomogram (OPG) was taken for hypodontia patient only. Saliva was collected for genetic analysis. Direct sequencing was performed by using exon 2and 3 of PAX9 gene.